SUNDAY SCHOOL’S PERFORMANCE ANALYSIS OF CHURCH X BANDUNG - Sihotang, Sri Malasari; Pritasari, Adita (Journal of Business and Management, 2018)
Abstract. Sunday school is a service ground that is based on the calling of heart and as a volunteer to serve God. This does not mean that Sunday school is a learning program that there is no foundation of vision and mission. However, teachers should have good self-commitment, competence, and teaching ability that meet the needs of the child. Church X Bandung has a training program set up to foster and support Sunday school teachers, but not running well. Actually the church often thinks that guiding the Sunday school teacher does not really matter, so that provide training with the concept that is not matching on target and the result in the performance or learning process is often happened. Therefore, this study aims to determine the type of competence that should be possessed by the Sunday school teacher and how to develop it in teaching and educating children to make Sunday school performance more running effectively. This research uses narrative method by understanding the perspective of resource based on story (narrative) about Sunday school from teacher, child, parent, and pastor that delivered through interview. The results of the Sunday school performance evaluation show that Sunday school teachers need training to improve the teaching quality. Researchers recommend a solution for Church X to conduct regular training to find out the competencies required of current teachers and how to improve Sunday school's performance.Keywords: Church X Bandung, Competency, Sunday school's performance, Sunday school teacher, Training.Â